2007
DOI: 10.1111/j.1365-2389.2006.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of phthalic acid and salicylic acid by two variable charge soils as influenced by sulphate and phosphate

Abstract: Low-molecular-weight (LMW) organic acids exist widely in soils, especially in the rhizosphere, and the adsorption of these acids may affect their reactions in soils. The adsorption behaviour of phthalic acid and salicylic acid by two variable charge soils (a Rhodic Ferralsol and a Haplic Acrisol) was investigated. Both soils exhibited great adsorption capacity for these organic acids, with a greater affinity for phthalic acid. The Rhodic Ferralsol adsorbed more organic acids of both kinds than the Haplic Acris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
(38 reference statements)
0
11
1
Order By: Relevance
“…The competition between salicylic acid and P for sorption sites in two variable-charge soils was documented as well by Xu et al [31]. On the other hand, Fox et al [27] compared 16 organic acids and found no significant differences between salicylic acid and water in P solubilization.…”
Section: Discussionmentioning
confidence: 80%
“…The competition between salicylic acid and P for sorption sites in two variable-charge soils was documented as well by Xu et al [31]. On the other hand, Fox et al [27] compared 16 organic acids and found no significant differences between salicylic acid and water in P solubilization.…”
Section: Discussionmentioning
confidence: 80%
“…The high rate application of P fertilizer generally causes P accumulation in soils. Phosphate is known to convey negative charges to the soil particle surface (Marchi et al, 2006;Antelo et al, 2007;Guan et al, 2007;Xu et al, 2007), which in turn will decrease the adsorption of anionic pesticides, such as 2,4-D (Vasudevan and Cooper, 2004) and glyphosate (Gimsing et al, 2004;Wang et al, 2005; and other anionic pollutants such as arsenate (Gao and Mucci, 2001). We found that P significantly affected the adsorption behaviors of TC on soils.…”
Section: Discussionmentioning
confidence: 81%
“…Salicylic or phthalic acids in solution were measured by ultraviolet spectroscopy with wavelength 304 nm for salicylic acid and 280 nm for phthalic acid, respectively [27]. The recovery of the acids was found to range from 97 to 103%.…”
Section: Methodsmentioning
confidence: 99%